The effect of previous SARS-CoV-2 infection on systemic immune responses in individuals with tuberculosis - Xavier, Mariana S.; Araujo-Pereira, Mariana; de Oliveira, Quezia M.; Sant’Anna, Flavia M.; Ridolfi, Felipe M.; de Andrade, Alice M. S.; Figueiredo, Marina C.; Sterling, Timothy R.; Gordhan, Bhavna G.; Kana, Bavesh D.; Andrade, Bruno B.; Rolla, Valeria C.; et al. (Frontiers in Immunology, 2024)
Background: The impact of previous SARS-CoV-2 infection on the systemic immune response during tuberculosis (TB) disease has not been explored. Methods: An observational, cross-sectional cohort was established to evaluate the systemic immune response in persons with pulmonary tuberculosis with or without previous SARS-CoV-2 infection. Those participants were recruited in an outpatient referral clinic in Rio de Janeiro, Brazil. TB was defined as a positive Xpert-MTB/RIF Ultra and/or a positive culture of Mycobacterium tuberculosis from sputum. Stored plasma was used to perform specific serology to identify previous SARS-CoV-2 infection (TB/Prex-SCoV-2 group) and confirm the non-infection of the tuberculosis group (TB group). Plasmatic cytokine/chemokine/growth factor profiling was performed using Luminex technology. Tuberculosis severity was assessed by clinical and laboratory parameters. Participants from TB group (4.55%) and TB/Prex-SCoV-2 (0.00% received the complete COVID-19 vaccination. Results: Among 35 participants with pulmonary TB, 22 were classified as TB/Prex-SCoV-2. The parameters associated with TB severity, together with hematologic and biochemical data were similar between the TB and TB/Prex-SCoV-2 groups. Among the signs and symptoms, fever and dyspnea were significantly more frequent in the TB group than the TB/Prex-SCoV-2 group (p≤0,05). A signature based on lower amount of plasma EGF, G-CSF, GM-CSF, IFN-α2, IL-12(p70), IL-13, IL-15, IL-17, IL-1β, IL-5, IL-7, and TNF-β was observed in the TB/Prex-SCoV-2 group. In contrast, MIP-1β was significantly higher in the TB/Prex-SCoV-2 group than the TB group. Conclusion: TB patients previously infected with SARS-CoV-2 had an immunomodulation that was associated with lower plasma concentrations of soluble factors associated with systemic inflammation. This signature was associated with a lower frequency of symptoms such as fever and dyspnea but did not reflect significant differences in TB severity parameters observed at baseline.